Tony solves the linear equation 3(x - 3) + 2x + 9 = 2x + 2(x - 1) using the step shown below.
Step 1: 3x - 3 + 2x + 9 = 2x + 2x - 1
Step 2: 5x + 6 = 4x - 1
Step 3: 5x - 4x = -1 - 6
Step 4: x = -7
a. He incorrectly combined like terms.
b He incorrectly applied the addition and subtraction properties of equality.
c He incorrectly applied the multiplication and division properties of equality.
d He distributed incorrectly.
because when you have numbers inside the parentheses, you have to multiply both of those numbers by the number to the right of the parentheses, not just the X.